2018
DOI: 10.1073/pnas.1802966115
|View full text |Cite
|
Sign up to set email alerts
|

In vivo replacement of damaged bladder urothelium by Wolffian duct epithelial cells

Abstract: The bladder's remarkable regenerative capacity had been thought to derive exclusively from its own progenitors. While examining consequences of DNA methyltransferase 1 () inactivation in mouse embryonic bladder epithelium, we made the surprising discovery that Wolffian duct epithelial cells can support bladder regeneration. Conditional inactivation in mouse urethral and bladder epithelium triggers widespread apoptosis, depletes basal and intermediate bladder cells, and disrupts uroplakin protein expression. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 30 publications
0
12
0
Order By: Relevance
“…Other fate‐mapping studies demonstrated that superficial cells were derived from proliferation of both basal cells and intermediate cells after injury 3,34‐36 . A more recent study showed that Wolffian duct epithelial cells can also repopulate injured bladders and restore a uroplakin barrier 37 . These conflicting evidence might be the results of heterogeneity and complexity of bladder urothelial cells.…”
Section: Discussionmentioning
confidence: 99%
“…Other fate‐mapping studies demonstrated that superficial cells were derived from proliferation of both basal cells and intermediate cells after injury 3,34‐36 . A more recent study showed that Wolffian duct epithelial cells can also repopulate injured bladders and restore a uroplakin barrier 37 . These conflicting evidence might be the results of heterogeneity and complexity of bladder urothelial cells.…”
Section: Discussionmentioning
confidence: 99%
“…Under uninjured conditions, the HZ may repress OB-ISC division, as severe HZ injury causes extreme OB-ISC hyperplasia and causes OB-ISCs to cross the midgut/hindgut boundary. Similar cross-tissue injury responses appear to occur in other animals following both injury (Joseph et al 2018) and disease (Badreddine and Wang 2010;Hvid-Jensen et al 2011). Going forward, the midgut/hindgut boundary provides an accessible model to study how tissues respond to injury across organ boundaries, and how disruption of such responses may influence disease progression.…”
Section: Modeling Injury Repair and Cancer Initiation In The Hindgutmentioning
confidence: 83%
“…Cre inducible R26R-LacZ or R26R-EYFP alleles were also incorporated to visualize Cremediated recombination. cDnmt1KO newborns do not survive more than a few minutes, are cyanotic and have severely hypoplastic lungs compared to controls (Joseph et al, 2018). DNMT1 protein is expressed throughout the urethral epithelium with the highest expression in prostatic buds.…”
Section: Results: Epithelial Dnmt1 Is Required For Prostatic Bud Formationmentioning
confidence: 99%
“…Prostatic gland genesis is not complete until approximately one month after birth but cDnmt1KO pups die soon after birth (Joseph et al, 2018). We therefore rescued E18.5 prostatic urethras from control and cDnmt1KO embryos and grafted them under the kidney capsule of intact male athymic nude mice for continued growth and development.…”
Section: Dnmt1 Expression Is Required For Prostate Glandular Developmentmentioning
confidence: 99%
See 1 more Smart Citation